1981
DOI: 10.1029/ja086ia07p05819
|View full text |Cite
|
Sign up to set email alerts
|

Conjugacy of electron microbursts and VLF chorus

Abstract: Information on the location of microburst source regions is limited. One measurement at L ≈ 8.5 placed the source within 4 RE of the ionosphere. Measurements at 5≲ L ≲6, though less conclusive, suggested that source regions may be located either near the equatorial plane or at higher magnetic latitudes along the field line. This paper reports simultaneous observations of bremsstrahlung X rays and VLF radiowave emissions that reveal a detailed correlation between electron microbursts precipitated in one hemisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 39 publications
1
46
1
Order By: Relevance
“…Chorus is a bursty whistler mode wave with elements of ∼0.1-1 s and has similar time scales as electron microbursts (Tsurutani and Smith, 1974). Moreover, the coincident occurrences between microburst and VLF chorus waves have given support to the idea that low energy microbursts are produced by wave-electron cyclotron resonance interactions (Rosenberg et al, 1981).…”
Section: Introductionmentioning
confidence: 82%
“…Chorus is a bursty whistler mode wave with elements of ∼0.1-1 s and has similar time scales as electron microbursts (Tsurutani and Smith, 1974). Moreover, the coincident occurrences between microburst and VLF chorus waves have given support to the idea that low energy microbursts are produced by wave-electron cyclotron resonance interactions (Rosenberg et al, 1981).…”
Section: Introductionmentioning
confidence: 82%
“…The cyclotron wave-particle interaction results in a decrease in the pitch angle of the resonant electrons and may lead to their precipitation (Foster and Rosenberg, 1976;Rosenberg et al, 1981). Electron precipitation can be monitored using a riometer, which indicates the degree of absorption of cosmic VHF radio noise due to charged particle den- .…”
Section: Observationsmentioning
confidence: 99%
“…The experimental observations included X-ray and VLF-wave measurements from a balloon near Roberval, and VLF data from a ground receiver at Siple. A detailed study of those events by Rosenberg et al (1981) concluded that the interactions were similar to those of . However, the X-ray precipitation at Siple was not measured during the events.…”
Section: Introductionmentioning
confidence: 96%
“…However, the X-ray precipitation at Siple was not measured during the events. Rosenberg et al (1981) also presented evidence of a spatial separation along the field line of the wavegrowth and pitch-angle scattering regions. Furthermore, to achieve agreement between the theoretical and observed time lags between VLF and X-ray bursts, they had to assume a non-negligible time delay in the pitch angle scattering process itself (-70 -80 milliseconds).…”
Section: Introductionmentioning
confidence: 99%